Hubungan Antara Rasa Takut Ibu Terhadap Efek Samping Pemasangan Kontrasepsi IUD - Aidha Rachmawati; Erda Restiya Agustin (IJMT : Indonesian Journal of Midwifery Today, 2022)
Side effects of contraception are a problem for the acceptors, because it is a psychological burden that must be borne, which ends in excessive worry and anxiety, so that they can experience discontinuation. The purpose of this study was to analyze the relationship between maternal fear and the side effects of inserting the IUD contraception. Analytical research method with cross sectional approach, dependent variable side effects, independent variable fear, population of 45 IUD acceptors, sampling technique with total sampling, and data analysis using chi square test, = 0.05. The results showed that there was a relationship between maternal fear and side effects of IUD insertion. It is hoped that IUD acceptors will increase their knowledge by actively participating in health education, especially contraceptive methods, so that acceptors can have a positive attitude and can manage the stress they experience when side effects arise.